2022
DOI: 10.1111/inm.13069
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19‐related discrimination, PTSD symptoms, and psychological distress in healthcare workers

Abstract: To date, little effort has been made to examine if frontline workers who deal with COVID‐19 patients are more likely to experience discrimination than second‐line workers. Also, little information has appeared on how COVID‐19‐related discrimination affects PTSD symptoms in healthcare workers. We aimed to examine the association between COVID‐19‐related discrimination and frontline worker status. We further aimed to examine how COVID‐19‐related discrimination was associated with PTSD symptoms and psychological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…For HCWs at a national medical institution designated for COVID-19 treatment, chronic physical conditions were significantly associated with depressive symptoms ( 18 ). In another survey, frontline workers had increased odds of COVID-19-related discrimination, which was associated with PTSD symptoms and psychological distress, compared with second-line workers ( 19 ). According to a multi-center collaborative survey, COVID-19-related discrimination was significantly associated with subsequent depression and suicidal ideation among HCWs ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…For HCWs at a national medical institution designated for COVID-19 treatment, chronic physical conditions were significantly associated with depressive symptoms ( 18 ). In another survey, frontline workers had increased odds of COVID-19-related discrimination, which was associated with PTSD symptoms and psychological distress, compared with second-line workers ( 19 ). According to a multi-center collaborative survey, COVID-19-related discrimination was significantly associated with subsequent depression and suicidal ideation among HCWs ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Selecting “yes” for either of these items was considered to experience COVID-19-related discrimination. These items were used based on past reports ( Do Duy et al, 2020 ; Narita et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…COVID-19-related discrimination against healthcare workers is reportedly linked to poorer mental health ( Labrague et al, 2021 ; Monterrosa-Castro et al, 2020 ; Narita et al, 2022 ; Shrestha et al, 2022 ). Specifically, cross-sectional studies showed that depression correlated with COVID-19-related discrimination ( Campo-Arias et al, 2021 ; Correia da Silva et al, 2022 ; Moro et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Associations of self-isolation, social support and coping strategies with depression and suicidal ideation in U.S. young adults during the COVID-19 pandemic Zui Narita 1 | Jordan Devylder 2,3 | Melissa Bessaha 4 | Lisa Fedina 5 have a detrimental impact on mental health during the pandemic, such as economic decline, unemployment, stigma, self-isolation and social distancing measures and a general decrease in socialization and access to support from others (Narita et al, 2022(Narita et al, , 2023Panchal et al, 2021;Robinson et al, 2022;Samji et al, 2022). Such stressors and how individuals respond to them might moderate the detrimental effect of the COVID-19 pandemic on mental health.…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…Evidence also suggests that the pandemic has harmed mental health in the general population (Xiong et al, 2020). Multiple factors are suggested to have a detrimental impact on mental health during the pandemic, such as economic decline, unemployment, stigma, self‐isolation and social distancing measures and a general decrease in socialization and access to support from others (Narita et al, 2022, 2023; Panchal et al, 2021; Robinson et al, 2022; Samji et al, 2022). Such stressors and how individuals respond to them might moderate the detrimental effect of the COVID‐19 pandemic on mental health.…”
Section: Introductionmentioning
confidence: 99%